2022
DOI: 10.1039/d1ea00045d
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol formation from gasoline and diesel vehicle exhaust under light and dark conditions

Abstract: Secondary organic aerosol (SOA) formed from vehicle exhaust contributes substantially to the atmospheric particulate matter in urban air but there still remain uncertainties in the simulation of the SOA by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 126 publications
(279 reference statements)
0
2
0
Order By: Relevance
“…Platt et al (2017) showed that both gasoline direct injection (GDI) and port fuel injection (PFI) gasoline vehicles produce significantly higher SOA compared to the latest-generation diesel vehicles equipped with a diesel oxidation catalyst (DOC) and a diesel particulate filter (DPF). The high SOA formation from gasoline vehicles has also been confirmed in several studies (e.g., Platt et al, 2013;Nordin et al, 2013;Gordon et al, 2014;Liu et al, 2015;Karjalainen et al, 2016;Saliba et al, 2017;Zhao et al, 2017;Ma et al, 2018;Pieber et al, 2018;Simonen et al, 2019;Roth et al, 2019;Morino et al, 2022;Hartikainen et al, 2023). The SOA produced from gasoline vehicles can be 1-2 orders of magnitude higher than the emitted POA (Platt et al, 2013;Gordon et al, 2014;Liu et al, 2015;Suarez-Bertoa et al, 2015;Karjalainen et al, 2016;Pieber et al, 2018;Kari et al, 2019).…”
Section: Introductionmentioning
confidence: 58%
“…Platt et al (2017) showed that both gasoline direct injection (GDI) and port fuel injection (PFI) gasoline vehicles produce significantly higher SOA compared to the latest-generation diesel vehicles equipped with a diesel oxidation catalyst (DOC) and a diesel particulate filter (DPF). The high SOA formation from gasoline vehicles has also been confirmed in several studies (e.g., Platt et al, 2013;Nordin et al, 2013;Gordon et al, 2014;Liu et al, 2015;Karjalainen et al, 2016;Saliba et al, 2017;Zhao et al, 2017;Ma et al, 2018;Pieber et al, 2018;Simonen et al, 2019;Roth et al, 2019;Morino et al, 2022;Hartikainen et al, 2023). The SOA produced from gasoline vehicles can be 1-2 orders of magnitude higher than the emitted POA (Platt et al, 2013;Gordon et al, 2014;Liu et al, 2015;Suarez-Bertoa et al, 2015;Karjalainen et al, 2016;Pieber et al, 2018;Kari et al, 2019).…”
Section: Introductionmentioning
confidence: 58%
“…19−22 Gentner et al 19 reported 2− 7 times more SOA for diesel vehicles than gasoline vehicles, and Tang et al 23 showed elevated IVOC emissions from in-use diesel vehicles that contribute to SOA growth. In contrast, Morino et al 24 showed more SOA for gasoline vehicles compared to diesel vehicles during chassis dynamometer testing. They attributed the differences in SOA formation to aromatic VOCs in gasoline exhaust compared with alkane IVOCs in diesel exhaust.…”
Section: ■ Introductionmentioning
confidence: 86%
“…SOA is a major constituent of ambient aerosol mass and forms in the atmosphere through oxidation reactions of VOC precursors with varying volatilities. , A number of studies have shown that organic compounds with intermediate volatilities (IVOCs) are important precursors of SOA formation. ,, Other studies have discussed the relative contribution of precursor emissions from gasoline and diesel vehicles on SOA production. Gentner et al reported 2–7 times more SOA for diesel vehicles than gasoline vehicles, and Tang et al showed elevated IVOC emissions from in-use diesel vehicles that contribute to SOA growth. In contrast, Morino et al showed more SOA for gasoline vehicles compared to diesel vehicles during chassis dynamometer testing. They attributed the differences in SOA formation to aromatic VOCs in gasoline exhaust compared with alkane IVOCs in diesel exhaust.…”
Section: Introductionmentioning
confidence: 87%
“…However, it has been shown that volatile organic compounds (VOCs), particularly single ring aromatics, emitted during driving or idling with a GDI vehicle form signicant SOA when oxidized in the atmosphere. [9][10][11][12] Nordin et al 2013 and Liu et al 2015 found that 60-90% of SOA formation could be assigned to C6-C10 aromatics for Euro 1-Euro 4 compliant gasoline cars. 13,14 Whilst these are likely Port Fuel Injection (PFI) engines the composition of the gasoline is still comparable.…”
Section: Introductionmentioning
confidence: 99%